New Acoustics Based on Metamaterials - Gan, Woon Siong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book highlights the acoustical metamaterials' capability to manipulate the direction of sound propagation in solids which in turn control the scattering, diffraction and refraction, the three basic mechanisms of sound propagation in solids. This gives rise to several novel theories and applications and hence the name new acoustics. As an introduction, the book mentions that symmetry of acoustic fields is the theoretical framework of acoustical metamaterials. This is then followed by describing that acoustical metamaterials began with locally resonant sonic materials which ushered in the concept of negative acoustic parameters such as mass density and bulk modulus. This complies with form invariance of the acoustic equation of motion which again exemplifies the symmetry property of acoustic fields.
Introduction -- Gauge Invariance Properties of Acoustic Fields -- Negative Refraction is a Special Case of Coordinates -- Transformation-Unified Theory of Negative Refraction and Acoustical Cloaking -- Three Basic Mechanisms of Sound Propagation in Solids and Fluids -- Revolution in Acoustic Devices by Metamaterial -- Scattering at different Layers of different Parities.-Diffraction Tomography by Negative Inclusions -- Vibration Propagation in Metamaterial Structures -- Seismic Metamaterials -- Phononic Crystals based Crystal Acoustics -- Metamaterials based Acoustic Waveguides -- Metamaterials Acoustic Filters -Application  to Communication -- Acoustical Cloaking of Underwater Objects-Submarines -- Acoustic Diodes -- Nonlinear Acoustics based on Metamaterials -- Phononics -- Nonlinear Phononic Crystals-Energy  Harvesting -- Fabrication of Nanometamaterials -- Artificial  Piezoelectricity -- Conclusions.
Keywords: Materials -- Analysis; Acoustical engineering; Mechanics, Applied; Solids; Acoustics; Characterization and Analytical Technique; Engineering Acoustics; Solid Mechanics; Acoustics